2003
DOI: 10.1038/sj.jhh.1001532
|View full text |Cite
|
Sign up to set email alerts
|

Sagittal abdominal diameter is associated with insulin sensitivity in Chinese hypertensive patients and their siblings

Abstract: The purpose of the study is to observe the relation between anthropometric measurements, focusing on sagittal abdominal diameter (SAD), and insulin sensitivity indices in Chinese hypertensive patients and their siblings. In total, 907 participants, 537 hypertensive and 370 nonhypertensive, from 311 Taiwanese families were drawn from the Stanford Asia and Pacific Program for Hypertension and Insulin Resistance for the study. The participants received anthropometric measurements and 75-g oral glucose tolerance t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
1
5

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 25 publications
2
13
1
5
Order By: Relevance
“…However, as Inuit are undergoing a dietary transition, which also involves decreases in physical activity due to modern-day conveniences and sedentary jobs, the rates of obesity and of obesity-related chronic diseases including type 2 diabetes mellitus (DM) are increasing (3)(4)(5). Therefore, an evaluation of the extent to which anthropometric measures relate to indices of insulin sensitivity (6,7) among Inuit, as has been shown among other populations (8)(9)(10), was conducted.…”
Section: Introductionmentioning
confidence: 99%
“…However, as Inuit are undergoing a dietary transition, which also involves decreases in physical activity due to modern-day conveniences and sedentary jobs, the rates of obesity and of obesity-related chronic diseases including type 2 diabetes mellitus (DM) are increasing (3)(4)(5). Therefore, an evaluation of the extent to which anthropometric measures relate to indices of insulin sensitivity (6,7) among Inuit, as has been shown among other populations (8)(9)(10), was conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Los estudios que citan en su metodología el equipo empleado en la medición del DAS se refieren al calibre abdominal Holtain-Kahn Abdominal Caliper ® (Holtain; Dyfed Wales, Reino Unido), con brazo móvil y precisión de 0,1 cm. Además del equipo descrito, para la medición es necesaria una mesa de examen rígida 12,13,18,21,22,[24][25][26]30,[36][37][38][39][40] . La medida del DAS se debe obtener en el milímetro más próximo, cuando el brazo móvil del compás toca levemente el abdomen, sin compresión, después del movimiento espiratorio normal.…”
Section: Protocolos De Medición Del Dasunclassified
“…La mayoría de los estudios utilizan la medida del DAS como un parámetro aislado para evaluar la adiposidad central 3,20,21,24,[28][29][30][38][39][40][41]50 . Sin embargo, en algunos estudios se evaluó el IS, también conocido como índice de diámetro abdominal (IDA) 13,18,27 o índice de diámetro sagital (IDS) 36 , a partir de una combinación del DAS con el Pmuslo.…”
Section: Utilización Del Das: Valor Absoluto Y Cálculo De íNdices O Iunclassified
“…The study population has been reported previously. 12,13 The SAPPHIRe Network consists of six field centres in San Francisco, Hawaii and Taiwan. In the present study, 228 (119 men, 109 women) hypertensive patients who received IST to evaluate their in vivo insulin sensitivity were included for analysis.…”
Section: Subjectsmentioning
confidence: 99%
“…12 Each subject was subjected to a 75 g oral glucose tolerance test (OGTT) thereafter. 13 Fasting blood samples were collected for the measurements of PG and insulin. Then, 75 g glucose monohydrate (in 300 ml water) was administered to the subject to drink off within 5 min.…”
Section: Clinical Examinationmentioning
confidence: 99%